Grassroots Cultural Policy for Water Management in Bangladesh - Hossain, Amzad; Marinova, Dora (IWA Publishing, 2012)
Rural Bangladesh's livelihood depends on water and the existing grassroots policy framework for sustainable water management (conservation and consumption) reflects a cultural unity within a country which is culturally very diverse. Extra-abundance or shortage of water supply is generally viewed as natural; however, prolonged or human caused water deficiency is treated as the retaliation of nature against anthropogenic transgression, which is often attributed to an act of climate change. The mostly uneducated rural people of multi-cultural Bangladesh live a simple lifestyle promoted by the country's inspiring Baul tradition, including water management. The Bauls religiously promote water conservation and are devoted to enhancing public understanding of the role of water. Spirituality can be the basis for sound water management as traditionally prevalent in rural Bangladesh's self-reliant lifestyle. Western culture and development treat water as an economic resource and commodity. Irreverence or ignorance of water related spirituality by modern societies is the fundamental reason for scarcity, pollution, over-extraction, mal-utilisation and aggressive politics of water. Values-driven water management is emphasised as the sustainability breakthrough and an essential requirement for proper development. Based on the Bangladeshi experience, the paper argues for a spirituality oriented educational policy to inform sustainable water management.